Frequency of Depression and its Severity Among Primary Caregivers of Psychoactive Substance use Patients - Muhammad Idrees, Hafiza Iqra Iqbal, Iram Asghar Gill, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to find out how depressed primary carers of psychoactive substance use patients. Study Design: Cross sectional/ Descriptive Place and Duration: Study was conducted at DHQ Hospital Jhang with duration of Dec 2020-Dec 2021. Methods: This study included a total of 90 patients of both genders. Patients ranged in age from 20 to 65 years old. Primary carers of patients who used psychoactive substances were included in the study. After receiving informed written consent, patients' detailed demographics such as age, sex, and BMI were collected. Depression, stress, and anxiety were measured in the cases that were enrolled. SPSS 22.0 was used to analyze all of the data. Results: Among 90 cases, number of males was 58 (64.4%) and females were 32 (35.6%). The mean age of the patients was 31.6±8.51 years and mean BMI of the patients was 23.03±13.61 kg/m2. Majority of the cases were from urban areas 61 (67.8%) and had poor socio-economic status 55 (61.1%). Frequency of married patients was 49 (54.4%) and 53 (58.9%) were literate. Frequency of depression was found among 85 (94.4%) cases, anxiety in 78 (86.7%) cases and stress in 74 (82.2%) patients. Among 85 cases of depression 65 (76.5%) patients had severe depression. Conclusion: According to the findings of this study, the carers of patients who used psychoactive substances exhibited severe depression. On the one hand, the severity of medication-related difficulties is clearly linked to the development of anxiety and depression to others.